Penentuan Frekuensi Perjalanan Angkutan Umum Batik Solo Trans untuk Mengoptimalkan Jumlah Pendapatan - Ayu Sally Damayanti; Yusuf Priyandari; Wakhid Ahmad Jauhari (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2012)
This research utilizes the rearrangement on trip frequency of Batik Solo Trans as the solution for increasing their daily revenue. The first phase of the trip rearrangement is identifying peak hours of Batik Solo Trans and analyzing data distribution of passengers’ quantity. Next, Monte Carlo simulation is applied for evoking the passenger quantity data as the basis on trip frequency calculation. There are three types of trip frequency which are calculated, minimum, maximum and service frequency. The service frequency is a threshold between revenue and operational cost. At the last phase, sensitivity analysis is applied on service frequency calculation. This research shows that a suggested frequency (service frequency) could be applied when tariff for a passengers and passenger quantity are remaining unchanged. Besides, if Batik Solo Trans still use the old trip frequency, it’s suggested that Batik Solo Trans considers rising the tariff.